ANALISIS MINAT BELAJAR SISWA MENGGUNAKAN MEDIA WORDWALL PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI SDN KONANG 2 - Hariyati, Annisa; Dwi Safitri; Hesty Widyaning Tyastuti; Lia Hadini; Novianti Romadani; Ziyanatul Fitriyah; Ika Dian Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore how the use of Wordwall as an instructional medium can enhance students’ learning interest in the Pancasila Education subject for third-grade students at SDN Konang 2. The research is grounded in the recognition of learning interest as a crucial internal factor that contributes to student success, as well as the necessity for engaging and interactive teaching strategies aligned with students’ needs and characteristics. A quantitative approach was employed, utilizing an experimental design involving both pretest and posttest measures. Data were collected through a closed-ended questionnaire using a Likert scale and analyzed using descriptive statistical methods. The questionnaire instrument was developed to assess four key dimensions of learning interest: enjoyment, curiosity, attention, and engagement during the learning process. The analysis revealed that all four indicators yielded high results, with an average percentage of 80.5%. These findings indicate that the integration of Wordwall, featuring content on the application of Pancasila values, effectively stimulates students’ interest and active participation in learning activities. Therefore, Wordwall can be considered an innovative and relevant learning tool that supports the demands of 21st-century education.